Combining familiarity and landscape features helps break down the barriers between movements and home ranges in a non‐territorial large herbivore. (23rd January 2017) - Marchand, Pascal; Garel, Mathieu; Bourgoin, Gilles; Duparc, Antoine; Dubray, Dominique; Maillard, Daniel; Loison, Anne
Summary: Recent advances in animal ecology have enabled identification of certain mechanisms that lead to the emergence of territories and home ranges from movements considered as unbounded. Among them, memory and familiarity have been identified as key parameters in cognitive maps driving animal navigation, but have been only recently used in empirical analyses of animal movements. At the same time, the influence of landscape features on movements of numerous species and on space division in territorial animals has been highlighted. Despite their potential as exocentric information in cognitive maps and as boundaries for home ranges, few studies have investigated their role in the design of home ranges of non‐territorial species. Using step selection analyses, we assessed the relative contribution of habitat characteristics, familiarity preferences and linear landscape features in movement step selection of 60 GPS‐collared Mediterranean mouflon Ovis gmelini musimon × Ovis sp. monitored in southern France. Then, we evaluated the influence of these movement‐impeding landscape features on the design of home ranges by testing for a non‐random distribution of these behavioural barriers within sections of space differentially used by mouflon. We reveal that familiarity and landscape features are key determinants of movements, relegating to a lower level certain habitat constraints (e.g. food/cover trade‐off) that we had previously identified as important for this species. Mouflon generally avoid crossing both anthropogenic (i.e. roads, tracks and hiking trails) and natural landscape features (i.e. ridges, talwegs and forest edges) while moving in the opposite direction, preferentially toward familiar areas. These specific behaviours largely depend on the relative position of each movement step regarding distance to the landscape features or level of familiarity in the surroundings. We also revealed cascading consequences on the design of home ranges in which most landscape features were excluded from cores and relegated to the peripheral areas. These results provide crucial information on landscape connectivity in a context of marked habitat fragmentation. They also call for more research on the role of landscape features in the emergence of home ranges in non‐territorial species using recent methodological developments bridging the gap between movements and space use patterns. Abstract : Revealing memory/familiarity preferences and the overwhelming influence of landscape features on the spatial ecology of Mediterranean mouflon, this paper provides crucial information on landscape connectivity in a context of marked habitat fragmentation and could help identifying the mechanisms underlying the emergence and maintenance of home ranges in non‐territorial animals.